2014
DOI: 10.3892/mmr.2014.2054
|View full text |Cite
|
Sign up to set email alerts
|

Cholera toxin, a typical protein kinase A activator, induces G1 phase growth arrest in human bladder transitional cell carcinoma cells via inhibiting the c-Raf/MEK/ERK signaling pathway

Abstract: The biotoxin cholera toxin has been demonstrated to have anti-tumor activity in numerous types of cancer, including glioma. However, the role of cholera toxin in the tumorigenesis of transitional cell carcinoma (TCC), the most common malignant tumor of the bladder, remains to be elucidated. To address this, in the present study, two TCC cell lines, T24 and UM-UC-3, were treated with cholera toxin [protein kinase A (PKA) activator] and KT5720 (PKA inhibitor). Cell survival and proliferation, cell cycle alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Moreover, using two human bladder cell lines, T24 and UM-UC-3, it was demonstrated that CTX inactivates the c-Raf/Mek/Erk cascade, via the PKA-dependent c-Raf phosphorylation at Ser-43. This results in the downregulation of the expression of the regulatory molecules (cyclin D1, Cdk4, and Cdk6), followed by the G1 phase arrest (Figure 3; Zheng et al, 2014). …”
Section: Bacterial Cyclomodulinsmentioning
confidence: 99%
“…Moreover, using two human bladder cell lines, T24 and UM-UC-3, it was demonstrated that CTX inactivates the c-Raf/Mek/Erk cascade, via the PKA-dependent c-Raf phosphorylation at Ser-43. This results in the downregulation of the expression of the regulatory molecules (cyclin D1, Cdk4, and Cdk6), followed by the G1 phase arrest (Figure 3; Zheng et al, 2014). …”
Section: Bacterial Cyclomodulinsmentioning
confidence: 99%
“…Mutation of Braf gene in bladder cancer is an infrequent event [34], however, Ras mutation, which act upstream of Braf, or Ras pathway has been shown to play an important role in bladder cancer tumorigenesis [35], while MEK inhibitor, PD-0325901, has been shown to suppress bladder tumor growth in a patient-derived xenograft model [36] and the inhibition of Raf/MEK/ERK pathway through Cholera toxin also resulted in growth arrest in cell line model [37]. In this study, we found that vemurafenib, a Braf inhibitor, and trametinib, a MEK inhibitor, both could reverse DAPK1-associated gene expression signature, by connectivity mapping.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Thus, through signal induction experiments, we investigated whether Au@Pt-NSs influenced the phosphorylation of ERK1/2, JNK1/2, p38, or AKT. Both EJ and HUCs were treated with Au@Pt-NSs at different concentrations (0, 0.1, 0.3, and 0.5 μM) for different periods (1,6,12, and 24 h) followed by immunoblotting.…”
Section: Au@pt-nss Induce the Phosphorylation Of P38 And Inhibit The mentioning
confidence: 99%
“…Bladder cancer cells react to chemotherapeutic reagents through the activation or inhibition of key signaling pathways, including MAPKs and PI-3K/AKT. [4][5][6][7] These molecular cues are transmitted to the nucleus by several steps of a signaling cascade, which redistributes the association of regulators of the cell cycle, including cyclin-dependent kinases (CDKs) and their binding partners, at certain cell cycle phases: G1, S, and G 2 /M. [8][9][10] Transition from G1 phase to S phase is determined by interactions among key regulators, including cyclin D/E and CDK4/6, CDK inhibitors (p21WAF1 and p27KIP1), and retinoblastoma protein (pRB).…”
Section: Introductionmentioning
confidence: 99%